Thermophilic biohydrogen production from optimized enzymatic pretreatment of palm oil mill effluent via box-behnken design - Izzi, A.Z.; Wan Ishak, W.M.F.; Yusuf, N.N.A.N.; Alenezi, Raslan.A.; Alias, N.A. (Elsevier, 2023)
The demand for energy is increasing continuously due to the vast developments in many ways of life. Palm oil mill effluent (POME) seems to be a good carbon feedstock for hydrogen generation in fermentation processes. A biological pretreatment was applied to degrade the lignocellulose biomass in the anaerobic digestion process and improve the bioenergy production yield; one of the techniques is to use enzymes. In this study, enzymatic pretreatment was applied to POME to determine the optimum process parameters for producing reducing sugars (RS) to be used as a substrate in biohydrogen production. The Box-Behnken design (BBD) was used to construct an experiment to optimize the pretreatment variables, such as reaction time (h), enzyme concentration ( w/v), and pH. The optimum experimental conditions were found to be 12 hr of reaction time, an enzyme concentration of 3.76 w/v, and pH 5. The result showed that POME treated with the optimal enzymatic pretreatment increased the RS content by 182. Next, thermophilic biohydrogen production using a pretreated substrate was carried out at a temperature of 55 °C, mixing speed of 150 rpm, Chemical Oxygen Demand (COD) concentration of 29,100 mg/L, seed content of 18.2, and initial pH 7.14. The biohydrogen production potential (Hmax) was significantly increased by 145 (177 mL H2/g reducing sugar) by using enzymatically pretreated POME as a substrate. This result indicated that the recovery of RS from recalcitrant POME via enzymatic pretreatment could enhance biohydrogen production. Hence, it is a useful proposal for further application in bioenergy conversion from organic waste.